Changing India - Manmohan Singh (OUP, 2019)
Volume 1: India's Export Trends and the Prospects for Self-Sustained Growth 0199489564/9780199489565 Volume 2: Early Thoughts on Trade and Development 0199489572/9780199489572 (ed. C. Rangarajan) Volume 3: The International Order and the Quest for Equity in Development 0199489580/9780199489589 (ed. K. Sundaram) Volume 4: Economic Reforms: 1991 and Beyond 0199489599/9780199489596 (eds. Santanu Singh & Nicholas Stern) Volume 5, Part 1: The Prime Minister Speaks - Part 1 0199489602/9780199489602 (ed. Rudrangshu Mukherjee) Volume 5, Part 2: The Prime Minister Speaks - Part 2 0199489610/9780199489619 (ed. Rudrangshu Mukherjee)